2022
DOI: 10.3390/rel13090836
|View full text |Cite
|
Sign up to set email alerts
|

Locality from Hybridization to Integration: Cultural Politics and Space Production of Taiwan Mazu Temples in Mainland China

Abstract: An upsurge in Taiwan-based Mazu temple buildings has been observed in China (Tianjin, Kunshan, and Xiamen, etc.) recently. This paper applies qualitative research methods, including participatory observation and semi-structured interviews, to explore the development of Mazu temples in Tianjin, Kunshan, and Xiamen, China in terms of cross-regional connectivity, materiality, and cross-regional locality, to explore the process of transplantation and construction in the mainland. This paper finds that Mazu culture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…A number of scholars have focused on topics related to Mazu's beliefs and the development of tourism resources (Shuo et al 2009; C.-P. Lin 2021; Zhang 2021), while others have devoted their attention to Mazu and literary production (Poceski 2015) and literary acceptance . Geographically, Mazu studies are most richly diversified in Taiwan (Park 2018;Tischer 2020;Zhou 2022), followed by East Asia (Sang 2016), including Japan (Ng Wai-ming 2020), South Korea (Moo 2017), and Southeast Asia , including Vietnam (Fraszczak 2018). However, there is little literature exploring themes related to the exchange of Mazu beliefs between China and Japan.…”
Section: Introductionmentioning
confidence: 99%
“…A number of scholars have focused on topics related to Mazu's beliefs and the development of tourism resources (Shuo et al 2009; C.-P. Lin 2021; Zhang 2021), while others have devoted their attention to Mazu and literary production (Poceski 2015) and literary acceptance . Geographically, Mazu studies are most richly diversified in Taiwan (Park 2018;Tischer 2020;Zhou 2022), followed by East Asia (Sang 2016), including Japan (Ng Wai-ming 2020), South Korea (Moo 2017), and Southeast Asia , including Vietnam (Fraszczak 2018). However, there is little literature exploring themes related to the exchange of Mazu beliefs between China and Japan.…”
Section: Introductionmentioning
confidence: 99%
“…With the intersection of the research paradigm of religion in geography, the content of the study of the geography of religion as a discipline was clearly identified in the 1980s (Sopher 1981). In recent years, spatial data on religion have often been used in geographic studies, and some religious studies have drawn on geographic research methods, with many developments in data-driven spatial perspectives on the study of religion emerging (Gregory 2003;Sunier 2013;Zhou 2022). Some scholars have explored the spatial evolution of religion and its causes based on the geographic information data of religious officially sacred sites (Song et al 2016;Zhu et al 2019;Jiang 2019;Liu and Wan 2022).…”
Section: Introductionmentioning
confidence: 99%